Penerapan Pendekatan Merdeka untuk Meningkatkan Kualitas Proses dan Hasil Belajar Mata Kuliah Patung Eksperimental: - - Taswadi; Hery Santosa; Zakaria Soekarya Soeteja (PTK: Jurnal Tindakan Kelas, 2025)
This research is motivated by the process of the results of the implementation of experimental sculpture lectures in 2024 which have not been maximized. It can be seen from the learning process that is less enthusiastic and the sculptures produced are not yet varied in terms of materials and techniques, so that the works produced are less varied and less creative. The purpose of this study is to analyze the application of the independent approach in increasing the level of activeness and achievement of student learning outcomes in the Experimental Sculpture course in the Fine Arts Education Study Program, Faculty of Art and Design Education, Indonesian Education University. The implementation of lectures by applying the independent approach can provide freedom for students to explore, innovate, and develop creativity through flexible and project-based learning methods. The research method used is classroom action research with qualitative and quantitative analysis. The results of the study prove that the application of the independent approach can increase student activeness in the learning process, and improve more creative and innovative sculpture art skills.